Usage-based perspective on argument realisation: A corpus study of Indonesian BUY verbs in applicative construction with -kan - Gede Primahadi Wijaya Rajeg; I Wayan Arka (Nusa, 2023)
This paper presents constructional and quantitative corpus analyses of the argument realisation of beli ‘buy’ in the base and applicative -kan across the active voice (AV) meNand passive voice (PASS) di- constructions. It shows that the presumed standard Double Object construction for the AV applicative membelikan is significantly less frequent than the Monotransitive one, suggesting (i) the more semantic effect of the applicative in making the peripheral argument semantically central/core for the verb regardless of its syntactic realisation, and (ii) the role of argument omission in language use. We also discovered that the PASS dibelikan has distinct semantic properties not attested in the AV, highlighting the semantic sensitivity of voice and the need to view PASS as an independent construction. Finally, we discuss factors motivating the alternative argument realisations.